The Influence Of Leadership, Workload, And Job Placement On Employee Performance At North Banjarbaru Community Health Center, Banjarbaru City - Siti Khadijah; Melania, Melania (Sean Institute, 2022)
This study aims to determine the effect of simultaneously, partially, and dominant variables of leadership variables, workload, and work placement on the performance of the employees of Puskesmas Banjarbaru Utara. The research population is 58 respondents. The results of the research on the analysis of the Simultaneous Regression Coefficient Test (Test F) show that all independent variables, namely leadership (X1), workload (X2), and work placement (X3) have a simultaneous effect on employee performance (Y). The results of the t-test of the leadership variable (X1). The results of the t-test of the workload variable (X2). The results of the t-test of the work placement variable (X3). Then all the independent variables partially have a significant effect on the performance of the employees of Puskesmas Banjarbaru Utara. The independent variable that has a dominant effect on the performance of the employees of North Banjarbaru Community Health Center is the workload variable (X2). The result of the Coefficient of Determination (Adjusted R square) test is 58.4%, which means that the employee's performance (Y) can be explained by the independent variable which has a strong influence, and the remaining 41.6% by other influences not included in this study with.